Triboelectric nanogenerator based on direct image lithography and surface fluorination for biomechanical energy harvesting and self-powered sterilization. (July 2022) - Feng, Hanfang; Li, Huayang; Xu, Jin; Yin, Yiming; Cao, Jinwei; Yu, Ruoxin; Wang, Bingxue; Li, Runwei; Zhu, Guang
Abstract: Due to the high electric output, triboelectric nanogenerators (TENG) have gained extensive attention in recent years for their abilities to power the wearable and portable electronic devices. Surface charge density and effective contact area are pivotal for the electric output of the TENG. In this work, the maskless direct image lithography (DIL) method with high precision and rapid prototyping was used to fabricate the polyurethane (PU) layers with surface microcones within 3 min for increasing the contact electrification area. After chemically modified with trichloro (1 H, 1 H, 2 H, 2 H-perfluorooctyl) silane (FOTS) vapor, the contact area further increases accompanying with the enlarged electron affinity difference because of the roughened morphology in micro-nanoscale and the introduced surface fluorine. The TENG based on PU and fluorinated polyurethane (F-PU) layer with microcones can achieve a high current of 22 μA, which is 5 times higher than that of the flat PU and F-PU layers. The microcones, surface roughened morphology and fluorine on the microcones have conjunct effects on the enhancement of electric output. Moreover, because of the customizability of DIL method and the prominent stability and favorable flexibility of PU and F-PU layers, the TENG can be fabricated into different shapes to harvest mechanical energy from various human motions. Furthermore, when the TENG was connected with the cuprous oxide (Cu2 O) nanowire electrode and served as the electric supply, the antibacterial and antifungal properties of the nanowire show obvious enhancement. Thus, this work provides a rapid and effective way to enhance the output of TENG from perspectives of surface microstructure design without any templates. Graphical Abstract: ga1 Highlights: Direct image lithography was used to construct friction layers with microstructures. Fluorination process introduces fluorine along with further improved contact area. The TENG with microstructures can achieve a current of 22 μA. TENG with various shapes can harvest mechanical energy under different human motions. Cu2 O nanowires with TENG as electric supply show enhanced antibacterial property.